XÁC ĐỊNH ĐỒNG THỜI HÀM LƯỢNG MỘT SỐ VITAMIN NHÓM B BẰNG PHƯƠNG PHÁP ĐIỆN DI MAO QUẢN SỬ DỤNG DETECTOR ĐỘ DẪN KHÔNG TIẾP XÚC (CE-C4D) - Đặng, Thị Huyền My; Nguyễn, Quang Huy; Mai, Thị Thanh Tâm; Lê, Đức Dũng; Phạm, Hoàng Nguyên; Phạm, Thị Quỳnh; Nguyễn, Thị Minh Thư; Nguyễn, Thị Ánh Hường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SIMULTANEOUS DETERMINATION OF SOME B-GROUP VITAMINS IN DIETARY SUPPLEMENT SAMPLES BY CE-C4D The simultaneous determination of vitamin B1, vitamin B5, and vitamin B9 in dietary supplements was investigated by using capillary electrophoresis with capacitively coupled contactless conductivity detection (CE-C4D). Optimal conditions included: fused silica capillary inner diameter (ID) 50 µm and total length of 50 cm (effective length of 30 cm); electrolyte solution of 12 mM Arginine/Acetic acid/ 10% Acetonitrile; pH = 7.5; hydrodynamic injection at height of 15 cm in 30 s; separation voltage of 17 kV. Calibration curves were constructed over the range from 1.0 to 100 ppm (vitamin B1) and 2.0 ppm to 100 ppm (vitamin B5, vitamin B9) giving good linear correlation coefficients (R2 > 0.999). The limits of detection (LOD) for vitamin B1, B5 and B9 were 0.3, 0.5 and 0.6 ppm, respectively. The recoveries were ranging from 94.9% to 105.0%. The developed method was applied to simultaneously determine vitamin B1, B5 and B9 in 4 dietary supplement samples. The results of these vitamins in the samples differ from their labels by -11.67% to +12.50%. The CE-C4D results were compared with those obtained by reference UPLC-MS/MS method, showing good agreement between the two methods (relative error < 10.53%).